Oxalate disrupts monocyte and macrophage cellular function via Interleukin-10 and mitochondrial reactive oxygen species (ROS) signaling - Parveen Kumar; Emma Laurence; David K. Crossman; Dean G. Assimos; Michael P. Murphy; Tanecia Mitchell (2023)
Oxalate is a small compound found in certain plant-derived foods and is a major component of calcium oxalate (CaOx) kidney stones. Individuals that consume oxalate enriched meals have an increased risk of forming urinary crystals, which are precursors to CaOx kidney stones. We previously reported that a single dietary oxalate load induces nanocrystalluria and reduces monocyte cellular bioenergetics in healthy adults. The purpose of this study was to extend these investigations to identify specific oxalate-mediated mechanisms in monocytes and macrophages. We performed RNA-Sequencing analysis on monocytes isolated from healthy subjects exposed to a high oxalate (8 mmol) dietary load. RNA-sequencing revealed 1,198 genes were altered and Ingenuity Pathway Analysis demonstrated modifications in several pathways including Interleukin-10 (IL-10) anti-inflammatory cytokine signaling, mitochondrial metabolism and function, oxalic acid downstream signaling, and autophagy. Based on these findings, we hypothesized that oxalate induces mitochondrial and lysosomal dysfunction in monocytes and macrophages via IL-10 and reactive oxygen species (ROS) signaling which can be reversed with exogenous IL-10 or Mitoquinone (MitoQ; a mitochondrial targeted antioxidant). We exposed monocytes and macrophages to oxalate in an in-vitro setting which caused oxidative stress, a decline in IL-10 cytokine levels, mitochondrial and lysosomal dysfunction, and impaired autophagy in both cell types. Administration of exogenous IL-10 and MitoQ attenuated these responses. These findings suggest that oxalate impairs metabolism and immune response via IL-10 signaling and mitochondrial ROS generation in both monocytes and macrophages which can be potentially limited or reversed. Future studies will examine the benefits of these therapies on CaOx crystal formation and growth in vivo.